Legal nature of commercial concession contract (franchising) - Mentuh, Nataliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article is devoted to the analysis of the theoretical foundations for determining the legal nature of the commercial concession contract (franchising) and its features. An analysis of the current legislation regarding the determination of the legal nature of the commercial concession contract was carried out.It is argued that the issues of the legal nature of the commercial concession (franchising) contract remain debatable today. In addition, the institution of franchising in Ukraine needs a thorough rethinking and significant reformation, both theoretically and practically.It is substantiated that according to the analysis of the current legislation of Ukraine, the international law enforcement practice, a commercial concession is mediated by a franchise agreement. For this purpose, it is argued that the commercial concession agreement is equivalent to franchising agreements abroad.The author states in the article that according to the analysis of the current legislation of Ukraine, international law enforcement practice, a commercial concession is mediated by a franchise agreement.Considering the fact that the term "franchising" is unknown to the legislation of Ukraine, its equivalent is the concept of "commercial concession", and in order to avoid additional inconveniences at the stage of adapting franchising to the conditions of Ukrainian legislation, it is suggested that it is appropriate to use concepts commonly used in international practice. The statement on the adoption of the Law "On Franchising" with the aim of preventing confusion of concepts and strengthening the legislative framework was supported.Scientific positions on the interpretation of the concept of franchising and the features of the commercial concession contract are considered. Proposals for improving the theoretical foundations of the specified problem have been formulated.